2023
DOI: 10.1002/adma.202300616
|View full text |Cite
|
Sign up to set email alerts
|

Intramolecular‐Catalyzed Vitrimers with White‐Light Emission for Light‐Emitting Diode Encapsulation

Abstract: Currently available encapsulating materials for white light-emitting diodes (WLEDs) have certain limitations, such as the toxicity of phosphors and the non-recyclable nature of the encapsulating materials. In this study, relatively promising encapsulating materials with two significant advantages are developed. First, the chips can be directly encapsulated without phosphors using luminescent encapsulating materials. Second, the encapsulating materials can be reprocessed for recycling via intramolecular catalys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 61 publications
(71 reference statements)
0
2
0
Order By: Relevance
“…Nowadays near-ultraviolet (n-UV)/blue light-emitting diodes (LEDs) have become increasingly popular because of their many benefits over other solid-state lighting sources, including their long lifespan, stability, high efficiency, and environmental friendliness [1][2][3][4]. Commercial LED technology was first introduced in 1960, and with the 1997 release * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays near-ultraviolet (n-UV)/blue light-emitting diodes (LEDs) have become increasingly popular because of their many benefits over other solid-state lighting sources, including their long lifespan, stability, high efficiency, and environmental friendliness [1][2][3][4]. Commercial LED technology was first introduced in 1960, and with the 1997 release * Author to whom any correspondence should be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Since their commercial production in the 1940s, epoxy resins have gradually become an irreplaceable thermosetting plastic product in various fields. It is estimated that the global epoxy resin market capacity will reach 37.3 billion US dollars by 2025 . However, the fast development of epoxy resins faces tough barriers, especially the disposal of waste epoxy resins. , Owing to their permanent covalently cross-linked structures, the thermosetting epoxy resin products cannot be directly recycled like thermoplastics after their usage. , The commonly used disposal methods for these waste epoxy resin products are landfill and incineration, both of which are not environment friendly and economical. ,, To solve this issue, many researchers have constructed covalent adaptable network (CAN)-based epoxy resins using dynamic covalent bonds such as boroxines, imine bonds, boronic ester bonds, acetal linkages, and disulfide bonds. , , The resultant epoxy CANs typically exhibit promising self-healing ability, processability, and recyclability. ,,,,, Recently, many researchers have developed mechanically strong and tough epoxy CANs through the design of their chemical structures. For example, Xie and co-workers reported the design of a boronic ester bond-based epoxy CAN through the polymerization-induced nanoscale phase separation mechanism .…”
Section: Introductionmentioning
confidence: 99%
“…To realize such self-powered buildings, luminescent solar concentrators (LSCs) could be an ideal candidate that invisibly integrates the intricate architecture of photovoltaic (PV) generators into the edge of building glass. In such an architecture, the fluorescent material embedded in LSCs plays its role by absorbing the sunlight photons and re-emitting at a longer wavelength; the emitted photons could then be waveguided to PV cells attached on the perimeter to generate energy. Fluorescent materials can also be simultaneously used as phosphors in white light-emitting diodes (WLEDs). The development of highly efficient fluorescent materials that could be applied in both LSCs and WLEDs at the same time is highly desirable for self-powered buildings. Among various kinds of fluorophores as an appropriate candidate for both LSC and WLED applications, metal halide perovskite nanocrystals (PNCs) have proved their niche because of their unique features including size/composition-dependent spectral tunability, high brightness with photoluminescence quantum yields (PLQYs) up to 100%, and the ease with which they can be solution processed. So far, the research activity in perovskite-containing LSCs has been limited to the synthesis of single-phase (color) PNCs with a narrower emission and absorption range when compared to sunlight. For instance, Sargent et al reported iodine- and bromide-based quantum-well structure perovskites for LSCs with a narrow range of PL emission of 650–750 and 500–540 nm, respectively, resulting in a lower PV cell absorption and conversion efficiency. , Dopant-induced broadening of the emission band in perovskite was reported by Chen and co-workers, who produced Mn 2+ /Yb 3+ co-doped CsPbCl 3 with two emission ranges (550–700 nm and 950–1050 nm), but the absorption in the UV range remained a small proportion of the sunlight spectrum, thus also could not achieve the optimum utilization of sunlight .…”
Section: Introductionmentioning
confidence: 99%